1978
DOI: 10.1111/j.1751-1097.1978.tb07717.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin Cancer and Ultraviolet Radiation

Abstract: Abstract. A new model is presented for the calculation of the increased incidence of non‐melanoma skin cancer in Caucasians resulting from ozone reduction. The model postulates that the probability of first incidence of such skin cancer is distributed log‐normally as a function of total accumulated lifetime dose of harmful ultraviolet radiation. The effect on skin cancer incidence of an increase in harmful ultraviolet radiation due to ozone reduction can then be calculated directly from the extent to which ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The evaluation of UV‐A and UV‐B effects in human and animal skin is less ambiguous than in cells because of well‐defined end points that have been extensively studied (36–43). Erythema is an inflammatory response of the epidermis and dermis that acutely produces dilation of blood vessels and swelling of the skin and chronically produces hyperplasia and rearrangement of the skin architecture (44).…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of UV‐A and UV‐B effects in human and animal skin is less ambiguous than in cells because of well‐defined end points that have been extensively studied (36–43). Erythema is an inflammatory response of the epidermis and dermis that acutely produces dilation of blood vessels and swelling of the skin and chronically produces hyperplasia and rearrangement of the skin architecture (44).…”
Section: Discussionmentioning
confidence: 99%
“…Sunlight that reaches the earth's surface contains a large amount of ultraviolet light. Epidemiological and medical reports have indicated a significant relationship between skin cancer incidence and exposure to sunlight (Rundel and Nachtwey, 1978;Green and Medinger, 1978;Mandal et al, 1978;Mandal and Chatterji, 1980;Mefferth et al, 1976). They showed that UV light caused lipid peroxidation in human skin and that the products increased with increasing exposure to UV light or sunlight with advancing age.…”
Section: Introductionmentioning
confidence: 99%
“…1). As a result, the values given by Rundel and Nachtwey (1978) came down to between 2.5 and 3.1; those by Beadle (1978) to between 2.8 and 2.9. The other values mentioned were not checked in peer review.…”
Section: Influence Of Ozone Depletionmentioning
confidence: 99%
“…It is the biological amplification factor which is of most interest in the present connection; it will be denoted here by Ah, and values derived along various lines of reasoning will be summarized. Rundel and Nachtwey (1978) found values of Ab between 3.4 and 4.4 for non-melanoma skin cancer incidence in the USA. Beadle (1978) derived values between 4.0 and 5.1 for England and Wales.…”
Section: Influence Of Ozone Depletionmentioning
confidence: 99%
See 1 more Smart Citation